Spatial distribution of roadway environment features related to child pedestrian safety by census tract income in Toronto, Canada. Issue 3 (1st April 2019) - Rothman, Linda; Cloutier, Marie-Soleil; Manaugh, Kevin; Howard, Andrew William; Macpherson, Alison K; Macarthur, Colin
Abstract : Background: Investments in traffic calming infrastructure and other street design features can enhance pedestrian safety as well as contribute to the 'walkability' of neighbourhoods. Pedestrian–motor vehicle collisions (PMVCs) in urban areas, however, remain common and occur more frequently in lower income neighbourhoods. While risk and protective features of roadways related to PMVC have been identified, little research exists examining the distribution of roadway environment features. This study examined the relationship between roadway environment features related to child pedestrian safety and census tract income status in Toronto. Methods: Spatial cluster detection based on 2006 census tract data identified low-income and high-income census tract clusters in Toronto. Police-reported PMVC data involving children between the ages of 5 and 14 years were mapped using geographical information system. Also mapped were roadway environment features (densities of speed humps, crossing guards, local roads, one-way streets and missing sidewalks). Multivariate logistic regression was used to examine the relationship between roadway environment features (independent variables) and cluster income status (dependent variable), controlling for child census tract population. Results: There were significantly fewer speed humps and local roads in low-income versus high-income clusters. Child PMVC rates were 5.4 times higher in low-income versus high-income clusters. Conclusion: Socioeconomic inequities in the distribution of roadway environment features related to child pedestrian safety have policy and process implications related to the safety of child pedestrians in urban neighbourhoods.